2020
DOI: 10.2147/dmso.s247062
|View full text |Cite
|
Sign up to set email alerts
|

<p>MicroRNAs and Risk Factors for Diabetic Nephropathy in Egyptian Children and Adolescents with Type 1 Diabetes</p>

Abstract: Point your SmartPhone at the code above. If you have a QR code reader the video abstract will appear. Or use: https://youtu.be/f5M4-ruLFPo Purpose: Currently available markers for early detection of diabetic nephropathy (DN), the leading cause of end stage renal disease, have some limitations. There is insufficient evidence from previous studies about the role of several circulating microRNAs (miRNAs) in the early development of DN. This study aimed to describe the expression of miRNA-377, miRNA-93, miRNA-25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Moreover, the IL-6 could downregulate miR-200s, thereby inhibiting PI3K/AKT/GSK pathway activation and glycogen synthesis [ 31 ]. Similarly, miR-25, which acts as an antioxidant and as anti-apoptotic by activating the PTEN/Akt pathway, was downregulated in diabetics [ 15 ]. Furthermore, the results suggested that lncRNA MEG8 was downregulated in T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the IL-6 could downregulate miR-200s, thereby inhibiting PI3K/AKT/GSK pathway activation and glycogen synthesis [ 31 ]. Similarly, miR-25, which acts as an antioxidant and as anti-apoptotic by activating the PTEN/Akt pathway, was downregulated in diabetics [ 15 ]. Furthermore, the results suggested that lncRNA MEG8 was downregulated in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-375 can reduce insulin secretion by directly targeting 3′-phosphatidylinositol-dependent kinase 1 mRNA, which was a critical molecule in the intracellular phosphatidylinositol kinase (PI3K) pathway [ 14 ]. A recent study in Egyptian children found that miR-25 exerted antioxidant and anti-apoptotic effects through activating the PTEN/Akt pathway and was downregulated in diabetics [ 15 ]. In addition, lncRNA- p3134 was reported to have an important role in insulin signaling and glucose metabolism in pancreatic β cell in adults from Guangzhou, China [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of –omics and the public availability of numerous data sets from NASA GeneLab [ 173 ], allowed for some new discoveries including the importance of miRNAs. MiRNAs are small non-coding RNA molecules that are largely conserved throughout species and act as RNA-silencer, thus able to regulate post-transcriptional gene expression [ 174 ]; and can be associated with pathological conditions including cancer [ 175 , 176 , 177 ], diabetes [ 178 , 179 ], cardiovascular diseases [ 180 ], and viral infection [ 181 ]. Recent work has shown that both real and simulated spaceflight lead to an increased expression of several circulating miRNAs, now considered as a space-signature [ 172 , 182 ], and that antagomir supplementation could constitute preventive countermeasures for astronauts.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…To date, most evidence in this attractive research area is based on adult [ 36 , 37 , 38 , 39 , 40 ] and in vitro studies [ 27 , 28 , 41 , 42 ], while similar pediatric data are still limited [ 43 , 44 , 45 , 46 , 47 ]. Due to the urgent need for early identification of DN and of the fragmentariness of data in the field in childhood, we attempted to provide a comprehensive pediatric overview on the challenging role of miRNAs in DN.…”
Section: Introductionmentioning
confidence: 99%